Symbolic forms in ceramics, textiles and architecture. Representation of Wari ontology - Pacheco Acero, Rosario Alicia (2025)
In the Andean world, the feeling of community not only occurs among human beings but also encompasses nature such as places, plants, animals and even the Works made by man, living together in a balanced relationship in daily life. This process can be observed in the Wari, this relationship has produced a mimesis that manifests itself in the composition of forms and structures of their products and objects such as ceramics, textiles and architecture, with meanings to be interpreted and that must be understood as an expression of their ontology. This ontology manifests itself in its worldview, in its relationship with the earth, in its social organization and in the management of its territorial occupation. The article seeks to assess the agents and circumstances that produce the symbolic forms recognized in ceramics, textiles, architecture, as well as their meaning, in order to understand the culture present in Wari, as well as that of its ontology, which at the same time allows us to revalue Andean thought and, therefore, our identity expressed in its artistic production.